Prevalence, Management, and Outcome of Lupus Nephritis: A Ten Years Systematic Review - Setiawan Nathan, Daniel; Sanjaya, Charles (International Medical Journal Corp. Ltd, 2024)
Background: Lupus nephritis (LN) occurs in 50% of patients with SLE and is the most common, but not the only, cause of kidney injury in SLE. Men with SLE tend to have more aggressive disease with higher rates of renal and cardiovascular involvement and are more likely to develop kidney failure than women. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using PubMed, ScienceDirect, and SagePub, among other online venues. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Achieving a complete clinical response to treatment is critical to preserving long-term kidney health.